THE EFFECTIVENESS OF LOCAL WISDOM-BASED GAMES IN IMPROVING PHYSICAL FITNESS IN CHILDREN AGED 9 YEARS - kurniawan, Edi; Tangkudung, James; Widiastuti,; Candra WK, Dadang Warta; Alpen, Joni (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this research are to examine the effectiveness of local wisdom-based games in improving physical fitness in children aged 9 years, for 12 weeks and to investigate possibility of gender differences.Thisresearch used an experimental method involving 200 children aged 9 years. There were two groups in this research; the control group and the intervention group. The intervention group (n = 100; 50% boys and girls) received a 60-minute local wisdom-based games session every week which was provided by trained local instructor; the control group (n = 100; 50% boys and girls) did not receive additional training. Physical Fitness (PF) was assessed using a PF test before and after the intervention. In order to assess the effects of interventions and the possibility of gender differences, two group pretest-posttest design analysis was used in this research.The intervention group which was given the local wisdom-based games had better physical fitness than the control group. Most boys had higher improvement of physical fitness than girls. Moreover, boys did more activities than girls both moderate to strong activities.This research has proved that there is a significant effect of gender on physical fitness. The results also show the importance of interventions that can provide various benefits for developing and maintaining the right level of physical fitness for the next life.